Implementing VIPER for Imaging Cellular Proteins by Fluorescence Microscopy - Doh, Julia K. (Bio Protoc, 2019)
Genetically-encoded tags are useful tools for multicolor and multi-scale cellular imaging. Versatile Interacting Peptide (VIP) tags, such as VIPER, are new genetically-encoded tags that can be used in various imaging applications. VIP tags consist of a coiled-coil heterodimer, with one peptide serving as the genetic tag and the other (“probe peptide”) delivering a reporter compatible with imaging. Heterodimer formation is rapid and specific, allowing proteins to be selectively labeled for live-cell and fixed-cell imaging. In this Bio-Protocol, we include a detailed guide for implementing the VIPER technology for imaging receptors on live cells and intracellular targets in fixed cells. This protocol is complemented by two other Bio-Protocols outlining the use of VIPER ( Doh et al., 2019a and 2019b).